2016
DOI: 10.4067/s0717-92002016000200020
|View full text |Cite
|
Sign up to set email alerts
|

Fuelwood consumption pattern and its impact on forest structure in Kashmir Himalayas

Abstract: Patrón de consumo de leña y sus impactos en la estructura del bosque en Cachemira, Himalaya SUMMARYFuel wood is the major source of energy for the rural populations of Kashmir Himalayas. Immense fuel wood extraction from the local forests has resulted in deterioration of forest structure. Although, the fuel wood extraction pattern strongly impacts the structure and species composition of natural forests, detailed investigations remain scarce. The current research was designed to quantify fuel wood consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Studies that observed local or regional-level forest degradation linked to fuelwood harvest have concluded that degradation is due to the intersection of diverse factors, including socioeconomic factors like rapid population growth, changing labor supplies, and global markets, as well as environmental factors like low tree density and climactic conditions (Arnold et al, 2006;Mills Busa, 2013;Shaheen et al, 2016). When firewood becomes scarce due to demand that outpaces environmental capacity, rural households will employ a suite of coping strategies, including traveling longer distances to harvest dead wood, harvesting live trees, cooking less frequently or cooking food of lower nutritional value, and cooking with extended family to pool firewood resources (Leach and Mearns, 1988;Dewees, 1989).…”
Section: Firewood and Rural Developmentmentioning
confidence: 99%
“…Studies that observed local or regional-level forest degradation linked to fuelwood harvest have concluded that degradation is due to the intersection of diverse factors, including socioeconomic factors like rapid population growth, changing labor supplies, and global markets, as well as environmental factors like low tree density and climactic conditions (Arnold et al, 2006;Mills Busa, 2013;Shaheen et al, 2016). When firewood becomes scarce due to demand that outpaces environmental capacity, rural households will employ a suite of coping strategies, including traveling longer distances to harvest dead wood, harvesting live trees, cooking less frequently or cooking food of lower nutritional value, and cooking with extended family to pool firewood resources (Leach and Mearns, 1988;Dewees, 1989).…”
Section: Firewood and Rural Developmentmentioning
confidence: 99%
“…In these situations, people have difficulty earning income to meet the costs of health care, rent, education and electricity. In the same vein, Mitchell (2004) and Shaheen et al (2016), working on data from Kenya, Congo and Pakistan obtained through focus groups, found that NTFP consumption has positive effects on deforestation and forest degradation, which are not conducive to improving people's living conditions. Two lessons can be drawn from the theoretical and empirical literature.…”
Section: Review Of the Literaturementioning
confidence: 98%
“…The second lesson is that the results in the literature are nonlinear. Some authors (Tabuna, 1999;Koffi et al, 2017) believe that NTFP consumption tends to improve human development, and others (Loubelo & Mialoundama, 2002;Koubouana, 2008;Shaheen et al, 2016) believe that it does not allow populations to cope with urgent and unpredictable household problems (such as health care, water, education and electricity).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In the Himalayan region, fuel wood is the primary form of biomass energy. It is used for lightening, heating and cooking activities (Dhanai et al, 2014;Shaheen et al, 2016;Singh et al, 2021). Consumption of fuel wood is responsible for severe environmental problems including deforestation, the land degradation and contributes to climate change.…”
Section: Review Of Literaturementioning
confidence: 99%